Infiltrated IL-17A-producing gamma delta T cells play a protective role in sepsis-induced liver injury and are regulated by CCR6 and gut commensal microbes - Wan, Jian; Zhang, Qian; Hao, Yilong; Tao, Zhang; Song, Wei; Chen, Song; Qin, Long; Song, Weidong; Shan, Yi (Frontiers in Cellular and Infection Microbiology, 2023)
Sepsis is a common but serious disease in intensive care units, which may induce multiple organ dysfunctions such as liver injury. Previous studies have demonstrated that gamma delta ( T cells play a protective role in sepsis. However, the function and mechanism of  T cells in sepsis-induced liver injury have not been fully elucidated. IL-17A-producing  T cells are a newly identified cell subtype. In this study, we utilized IL-17A-deficient mice to investigate the role of IL-17A-producing  T cells in sepsis using the cecum ligation and puncture (CLP) model. Our findings suggested that these cells were the major source of IL-17A and protected against sepsis-induced liver injury. Flow cytometry analysis revealed that these  T cells expressed V4 TCR and migrated into liver from peripheral post CLP, in a CCR6-dependent manner. When CLP mice were treated with anti-CCR6 antibody to block CCR6-CCL20 axis, the recruitment of V4+  T cells was abolished, indicating a CCR6-dependent manner of migration. Interestingly, pseudo germ-free CLP mice treated with antibiotics showed that hepatic IL-17A+  T cells were regulated by gut commensal microbes. E.coli alone were able to restore the protective effect in pseudo germ-free mice by rescuing hepatic IL-17A+  T cell population. In conclusion, our research has shown that V4+ IL-17A+  T cells infiltrating into the liver play a crucial role in protecting against sepsis-induced liver injury. This protection was contingent upon the recruitment of CCR6 and regulated by gut commensal microbes.